Battery

By using low-porosity solid cathode and low polysulfide solubility liquid electrolyte in lithium-sulfur batteries, the performance problems caused by high polysulfide solubility in traditional lithium-sulfur batteries are solved, and high energy density, long cycle life and improved safety are achieved.

CN119890439APending Publication Date: 2025-04-25JOHNSON MATTHEY PLC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510047193.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-09-14
Filing Date
2019-09-13
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Due to the high solubility of polysulfides in electrolytes, traditional lithium-sulfur batteries lead to reduced circulation performance, reduced available capacity, shortened cycle life and reduced Coulomb efficiency.

Method used

A solid cathode with low porosity and a liquid electrolyte with low polysulfide solubility are used to combine the redox active sulfur component to ensure good interface contact between the electrolyte and each electrode.

Benefits of technology

High weight-volume energy density, high cycle life, improved safety characteristics, improved Coulomb efficiency and beneficial voltage distribution curves are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005238829970000011
    Figure HDA0005238829970000011
  • Figure HDA0005238829970000021
    Figure HDA0005238829970000021
  • Figure HDA0005238829970000031
    Figure HDA0005238829970000031
Patent Text Reader

Abstract

An electrochemical cell comprises an anode comprising lithium or sodium metal or a lithium or sodium metal alloy; an ionically conductive cathode comprising an electroactive sulfur material; and a liquid electrolyte comprising at least one lithium salt or at least one sodium salt, wherein the electrolyte has a polysulfide solubility of less than 500 mM.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application with an application date of September 13, 2019, application number 201980075030.X, and invention name “Battery”. Technical Field

[0002] The present invention relates to a battery, in particular to a lithium-sulfur battery. Background Art

[0003] Secondary batteries such as lithium-sulfur batteries can be charged by applying an external current to the battery. This type of rechargeable battery has a wide range of potential applications. Important considerations when developing lithium-sulfur secondary batteries include weight and volume energy, cycle life, and battery assembly convenience. Another example of a secondary battery is a sodium-sulfur battery.

[0004] A typical lithium-sulfur battery comprises an anode (negative electrode) formed of lithium metal or a lithium metal alloy and a cathode (positive electrode) formed of elemental sulfur or other electroactive sulfur-containing materials. Sulfur or other electroactive sulfur-containing materials are mixed with a conductive material such as carbon to improve their conductivity.

[0005] Traditionally, high-energy lithium-sulfur batteries utilize liquid electrolytes. The positive electrode typically contains carbon mixed with or doped with sulfur. During discharge, the electroactive sulfur material (e.g., elemental sulfur) is reduced to lithium polysulfide species S n 2- (n≥2, for example, n=2-8). These species are generally soluble in the electrolyte. In the second stage of discharge, the polysulfide is reduced to insoluble lithium sulfide Li2S. When the battery is charged, the two-stage mechanism occurs in reverse, where the lithium sulfide is oxidized to lithium polysulfide species, and then oxidized to sulfur. However, the shuttling of polysulfides in the electrolyte caused by the high solubility of polysulfides can affect the cycle performance and may reduce the coulombic efficiency. Specifically, during the cycling of conventional lithium-sulfur batteries, the concentration of polysulfide species increases in conventional electrolyte formulations due to the high solubility of these polysulfide species in the electrolyte. This process complicates the operation of conventional lithium-sulfur batteries and results in a reduction in available capacity (available usable energy), a shortened cycle life, and a reduction in coulombic efficiency.

[0006] An alternative to conventional lithium-sulfur batteries are all-solid-state lithium-sulfur (ASSLiS) batteries. Instead of the liquid electrolyte present in "conventional" lithium-sulfur batteries, these contain a solid electrolyte, such as a solid polymer or ceramic electrolyte. The use of solid electrolytes can be advantageous in terms of safety and volumetric / gravimetric energy density. The use of all-solid-state batteries avoids the formation of solvated polysulfide species in the liquid electrolyte, and therefore avoids the problems associated with the presence of these species. Therefore, in theory, all-solid-state lithium-sulfur batteries can achieve high gravimetric and volumetric energies. However, ASSLiS batteries suffer from significant problems such as poor interfacial contact between the electrolyte and the electrodes.

[0007] In view of the above, there is still a need for high-energy lithium-sulfur batteries that can solve the above problems. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Various aspects of the invention are described by way of example and with reference to the accompanying drawings, in which:

[0009] Figure 1 Electrochemical performance data are shown for a cell comprising a conventional sulfur cathode, a liquid electrolyte comprising a lithium salt at a concentration above 75% of its saturation concentration, and a lithium metal foil anode.

[0010] Figure 2 Electrochemical performance data of a cell according to the invention are shown.

[0011] Figure 3 Shows Figure 1 and Figure 2 Comparison of the cycle 2 discharge curves of the electrochemical performance data. DETAILED DESCRIPTION

[0012] Before describing the specific embodiments of the present invention, it should be understood that the present disclosure is not limited to the specific batteries, methods or materials disclosed herein. It should also be understood that the terms used herein are only used to describe specific embodiments and are not intended to be limiting, because the scope of protection will be defined by the claims and their equivalents.

[0013] In describing and claiming the batteries and methods of the present invention, the following terminology will be used: the singular forms "a," "an," and "the" include the plural forms unless the context clearly dictates otherwise. Thus, for example, reference to "a cathode" includes reference to one or more of such elements.

[0014] According to one aspect of the present invention, there is provided an electrochemical cell comprising:

[0015] an anode comprising lithium or sodium metal or a lithium or sodium metal alloy;

[0016] an ionically conductive cathode comprising an electroactive sulfur material; and

[0017] A liquid electrolyte comprising at least one lithium salt or at least one sodium salt, wherein the polysulfide solubility of the electrolyte is less than 500 mM.

[0018] The battery according to the present invention combines the benefits associated with conventional lithium-sulfur batteries and all-solid-state lithium-sulfur batteries. First, the use of a low-porosity solid cathode (i.e., a cathode structure having a low interfacial contact area between the electrolyte component and the cathode) together with a redox-active sulfur component that undergoes reduction and oxidation reactions without forming soluble intermediate polysulfide species can result in a high-energy lithium-sulfur battery. Second, the use of a liquid electrolyte with low solubility for lithium polysulfide species can ensure good interfacial contact between the electrolyte and each electrode. Benefits derived from this type of hybrid liquid / solid-state battery include high gravimetric-volumetric energy, high cycle life, improved safety characteristics, improved coulombic efficiency, and a beneficial voltage profile controlled by a BMS (battery management system).

[0019] According to another aspect of the present invention, there is provided an electrochemical cell comprising:

[0020] an anode comprising lithium or sodium metal or a lithium or sodium metal alloy;

[0021] an ionically conductive cathode comprising an electroactive sulfur material;

[0022] A liquid electrolyte comprising at least one lithium salt or at least one sodium salt, wherein the concentration of the at least one lithium salt or sodium salt in the electrolyte is at least 75% of the saturation concentration of the electrolyte.

[0023] Electrochemical Cells

[0024] The electrochemical cell according to the present invention may be a lithium-sulfur cell. A further example of an electrochemical cell according to the present invention is a sodium-sulfur cell. The lithium-sulfur cell may comprise a lithium anode and a cathode comprising an electroactive sulfur material such as elemental sulfur. The electrolyte may comprise at least one solvent or ionic liquid and a salt, such as a lithium salt. In another example, the electrochemical cell is a sodium-sulfur cell. In the case where the electrochemical cell is a sodium-sulfur cell, the cell may comprise a sodium anode and a cathode comprising an electroactive sulfur material such as elemental sulfur. The electrolyte may comprise at least one solvent or ionic liquid and a salt, such as a sodium salt.

[0025] anode

[0026] In a lithium-sulfur battery, the lithium anode comprises an electroactive matrix containing lithium. The electroactive matrix may comprise lithium metal or a lithium metal alloy. Preferably, the electroactive matrix comprises a foil formed of lithium metal or a lithium metal alloy. Examples of lithium alloys include lithium-aluminum alloys, lithium-magnesium alloys, and lithium-boron alloys. Lithium metal foil is preferably used. In the case where the battery is a sodium-sulfur battery, the anode comprises sodium metal or a sodium metal alloy. Preferably, the anode comprises a foil formed of sodium metal or a sodium metal alloy. Examples of sodium alloys include sodium-aluminum alloys, sodium-magnesium alloys, and sodium-boron alloys. Sodium metal foil is preferably used.

[0027] cathode

[0028] The cathode of the electrochemical cell comprises an electroactive sulfur material. The cathode is ionically conductive, i.e., it is capable of conducting ions (i.e., alkali metal cations, Li + Or Na + ). Thus, the electrochemistry of the cell according to the present invention can be carried out with little or no dissolution of active species such as polysulfides in the dielectric. In one embodiment, 10% or less, preferably 5% or less, for example, 2% or less of the polysulfides formed during charge / discharge can be dissolved in the electrolyte. In one embodiment, no polysulfides are dissolved in the electrolyte. The chemistry involved in the charging and discharging of the cell according to the present invention is similar to the chemistry observed in all-solid-state lithium-sulfur cells, where polysulfides are not dissolved in the electrolyte.

[0029] The electroactive sulfur material may comprise elemental sulfur, sulfur-based organic compounds, inorganic compounds with sulfur, and sulfur-containing polymers. Preferably, elemental sulfur or Li2S is used. In one embodiment, the cathode comprises a sulfur-carbon composite material. The cathode may comprise an electroactive sulfur material that may also be ionically conductive. The material may comprise sulfur and other elements such as Li, Na, Mg, P, N, Si, Ge, Ti, Zr, Sn, B, A, F, Cl, Br, I, O, or any combination thereof. Examples of sulfur-containing materials that are also ionically conductive include LGPS, Li3PS4, or Li7P3S 11 In one embodiment, the cathode may comprise a sulfur-carbon composite material that is also ionically conductive.

[0030] The cathode may further comprise a solid conductive material. The solid conductive material may be any suitable conductive material. Preferably, the solid conductive material may be formed of carbon. Examples include carbon black, carbon fibers, graphene, reduced graphene oxide, and carbon nanotubes. Other suitable materials include metals (e.g., flakes, filings, and powders) and conductive polymers. Examples of conductive polymers include polypyrrole, polythiophene, polyaniline, polyacetylene, poly-p-phenylene vinylene, and poly (3,4-ethylenedioxythiophene). Carbon black is preferably used. In one embodiment, in the case where the cathode comprises a sulfur-carbon composite material, the cathode may be free of further solid conductive materials.

[0031] The cathode may also contain an ionically conductive material, in particular a solid Li + Or Na + Ion conductor. Ion conductive materials can have a conductivity greater than 10 at 25°C. -7 S / cm, for example, greater than 10 -6 S / cm bulk ionic conductivity. The cathode contains an electroactive ion conductive material such as Li3PS4 or Li x P y S z In some cases, no other ion conductive materials may be present. In some embodiments, the lithium ion conductive material comprises a ceramic material. The ceramic material may have a crystalline, polycrystalline, partially crystalline or amorphous structure. Suitable ceramic materials include, but are not limited to, oxides, carbonates, nitrides, carbides, sulfides, oxysulfides and / or oxynitrides of metals and / or metalloids. In some cases, the ceramic material comprises lithium. Non-limiting examples of suitable solid electrolytes with sufficient ionic conductivity can be produced by combinations of various lithium compounds, such as lithium-containing ceramic materials including lithium oxide (e.g., Li2O, LiO, LiO2, LiRO2, wherein R is scandium, yttrium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and / or lutetium), lithium carbonate (Li2CO3), lithium nitride (e.g., Li3N), lithium oxysulfide, lithium oxynitride, garnet-type lithium oxide (e.g., Li7La3Zr2O 12 )、Li 10 GeP2S 12 , lithium phosphorus oxynitride, lithium silicon sulfide, lithium germanium sulfide, lithium lanthanum oxide, lithium titanium oxide, lithium borosulfide, lithium aluminum sulfide, lithium phosphosulfide, lithium silicate, lithium borate, lithium aluminate, lithium phosphate, lithium halide and combinations thereof. In some cases, the ceramic material comprises lithium oxide, lithium nitride or lithium oxysulfide. In some embodiments, the ceramic comprises carbonate and / or carbide.

[0032] In some embodiments, the lithium ion conductive material can be selected from substances that can provide electron pairs (e.g., Lewis bases). Examples of suitable electron-donating materials include, but are not limited to, lithium oxides (e.g., Li2O, LiO, LiO2, LiRO2, wherein R is scandium, yttrium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, gadolinium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and / or lutetium), lithium carbonate (Li2CO3), lithium nitride (e.g., Li3N), lithium oxysulfide, lithium oxynitride, garnet-type lithium oxides (e.g., Li7La3Zr2O 12 ), Li 10 GeP2S 12 , lithium phosphorus oxynitride, lithium silicon sulfide, lithium germanium sulfide, lithium lanthanum oxide, lithium titanium oxide, lithium borosulfide, lithium aluminum sulfide, lithium phosphosulfide, lithium silicate, lithium borate, lithium aluminate, lithium phosphate, lithium halide, and combinations thereof.

[0033] Examples of ceramic materials that can be used as lithium ion conductive materials include lithium-containing oxides, such as Li 3.3 La 0.56 TiO3; sodium super ion conductor (Nasicon) structure (for example: LiTi(PO4)3); lithium ion conductor (LiSICON) (Li 14 Zn(GeO4)4); Li 10 GeP2S 12 ; Garnet: Li7La3Zr2O 12 ; other oxides, such as Al2O3, TiO2, ZrO2, SiO2, ZnO; sulfides, such as Li2S-P2S5; antiperovskites, such as Li3OCl; hydrides, such as LiBH4, LiBH4-LiX (X = Cl, Br, I), LiNH, LiNH2, Li3AlH6, Li2NH; borates or phosphates, such as Li2B4O7, Li3PO4, LiPON; carbonates or hydroxides, such as Li2CO3, LiOH; fluorides, such as LiF; nitrides, such as Li3N; sulfides; lithium borosulfide, lithium phosphosulfide, lithium aluminum sulfide, oxysulfide, praseodymium oxide. At least one of the ceramic materials described above, or a combination thereof, can be used. In sodium-sulfur batteries, any of these conductive materials can be used in an equal amount of sodium ions.

[0034] In some examples, the lithium ion conductive material can be formed from an inherently ion conductive polymer material, such as Nafion. Alternatively, a polymer blended with a lithium (or sodium) salt can also be used, which can achieve a conductivity greater than 10 -7S / cm bulk conductivity. Examples of suitable polymers include EO-based polymers (e.g., PEO); acrylate-based polymers (e.g., PMMA); polyamines (polyethyleneimine); siloxanes (poly(dimethylsiloxane)); polyheteroaromatic compounds (e.g., polybenzimidazole); polyamides (e.g., nylon), polyimides (e.g., Kapton); polyvinyl compounds (e.g., polyacrylamide, poly(2-vinylpyridine), poly(N-vinylpyrrolidone), poly(methyl cyanoacrylate), poly(vinyl acetate), poly(vinyl alcohol), poly(vinyl chloride), poly(vinyl fluoride); inorganic polymers (e.g., polysilanes, polysilazanes, polyphosphazenes, polyphosphonates); polyurethanes; polyolefins (e.g., polypropylene, polytetrafluoroethylene); polyesters (e.g., polycarbonates, polybutylene terephthalate). In one embodiment, a coblock polymer such as Nafion may be used. In one embodiment, the cathode comprises a combination of ceramic particles and one or more ion-conductive polymers.

[0035] In the cathode, electrons and ions can be conducted in the solid state. This allows electrochemical reactions to occur at the solid cathode during charge or discharge without forming soluble intermediates in the form of polysulfide species.

[0036] The cathode may further include a binder for bonding the cathode components together. The cathode may also bond the cathode components to a conductive current collector. In this case, the binder may provide improved mechanical strength to the cathode, or may improve the processability of the cathode. The binder may be a polymer binder, for example a polyether such as poly(ethylene oxide), polyethylene glycol, polypropylene glycol, polytetramethylene glycol (PTMG), polytetramethylene ether glycol (PTMEG).

[0037] The binder can be selected from halogenated polymers, and more preferably also selected from fluorinated polymers. Examples of suitable binders include polyvinylidene fluoride (PVDF), preferably in the alpha form, polytrifluoroethylene (PVF3), polytetrafluoroethylene (PTFE), copolymers of vinylidene fluoride and hexafluoropropylene (HFP) or trifluoroethylene (VF3) or tetrafluoroethylene (TFE) or chlorotrifluoroethylene (CTFE), fluoroethylene / propylene (FEP) copolymers, copolymers of ethylene and fluoroethylene / propylene (FEP) or tetrafluoroethylene (TFE) or chlorotrifluoroethylene (CTFE), perfluoropropyl vinyl ether (PPVE), perfluoroethyl vinyl ether (PEVE), and copolymers of ethylene and perfluoromethyl vinyl ether (PMVE) or blends thereof.

[0038] Other examples of suitable binders include polyacrylonitrile, polyurethane, PVDF-acrylic acid copolymer; polyacrylic acid, polyimide and polyvinyl alcohol. Further suitable binders include rubber (such as styrene-butadiene rubber), cellulose (such as carboxymethyl cellulose) or gelatin.

[0039] In some embodiments, the binder is selected from at least one of PEO, PVDF, Nafion, polypyrrole, polythiophene, polyaniline, polyacetylene, polyphenylene vinylene, poly(3,4-ethylenedioxythiophene), and polyphenylene sulfide. For example, the binder may include polyethylene oxide or PVDF.

[0040] The cathode may include 0.05 wt%-20 wt%, preferably 0.5 wt%-10 wt%, for example 1 wt%-5 wt%, for example 2 wt%-3 wt% of the binder, based on the total weight of the cathode.

[0041] Electrolytes

[0042] The electrolyte according to the present invention can be a liquid electrolyte. Since the electrolyte wets the cathode and anode, the liquid electrolyte provides good physical contact between the electrolyte and the electrode. This is in contrast to all-solid-state batteries, in which the solid electrolyte cannot provide satisfactory interface contact between the electrolyte and the anode / cathode due to lack of wetting. This is a particular problem during the cycling of ASSLiS batteries when volume changes occur in the anode and cathode due to reactions occurring during charging or discharging during cycling. Due to these volume changes, it is extremely challenging to maintain close contact at the anode-electrolyte and cathode-electrolyte interfaces.

[0043] Any suitable solvent system or liquid or gel or a mixture of liquid and / or gel can be used for the electrolyte. The electrolyte is liquid within the operating temperature range of the battery, which can be -30-120°C, preferably -10-90°C, for example, 0-60°C. The operating pressure of the battery can be 5mbar-100bar, preferably 10mbar-50bar, for example 100mbar-20bar. In one example, the battery can be operated at room temperature and atmospheric pressure. The high concentration electrolyte according to the present invention means that the electrolyte has a lower vapor pressure than a standard electrolyte. Therefore, the battery according to the present invention can perform better than a standard lithium-sulfur battery at low pressure. The liquid electrolyte can be a gel electrolyte.

[0044] Suitable organic solvents for use in the electrolyte are ethers (e.g. linear ethers, diethyl ether (DEE), diethylene glycol dimethyl ether (2-methoxyethyl ether), tetraethylene glycol dimethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, dimethoxyethane (DME), dioxolane (DIOX)); carbonates (e.g. dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methylpropyl carbonate, ethylene carbonate (EC), propylene carbonate (PC); sulfones (e.g. dimethyl sulfone (DMS), ethyl methyl sulfone (EMS), tetramethyl sulfone (TMS)); esters (e.g. methyl formate, ethyl formate, methyl propionate, methylpropyl propionate , ethyl propyl propionate, ethyl acetate and methyl butyrate); ketones (e.g., methyl ethyl ketone); nitriles (e.g., acetonitrile, propionitrile, isobutyronitrile); amides (e.g., dimethylformamide, dimethylacetamide, hexamethylphosphoramide, N,N,N,N-tetraethylsulfonamide); lactams / lactones (e.g., N-methyl-2-pyrrolidone, butyrolactone); ureas (e.g., tetramethylurea); sulfoxides (e.g., dimethyl sulfoxide); phosphates (e.g., trimethyl phosphate, triethyl phosphate, tributyl phosphate); phosphoramides (e.g., hexamethylphosphoramide). Further suitable solvents include toluene, benzene, heptane, xylene, dichloromethane and pyridine.

[0045] Any ether, carbonate, sulfone, ester, ketone, nitrile, amide, lactam, urea, phosphate, phosphoramide can be fluorinated. An example of a fluorinated ether is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0046] Any combination of one or more of the above solvents may be included in the electrolyte.

[0047] In alternative embodiments, the electrolyte may include one or more ionic liquids as solvents. The ionic liquids may include salts containing organic cations such as imidazolium, ammonium, pyrrolidinium and / or organic anions such as bis(trifluoromethanesulfonyl)imide TFSI. - 、Bis(fluorosulfonyl)imide FSI - , trifluoromethanesulfonate, tetrafluoroborate BF4 - , dicyandiamide DCA - 、Chloride ion Cl -. The ionic liquid is liquid at room temperature (20°C). Examples of suitable ionic liquids include (N,N-diethyl-N-methyl-N(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl), N,N-diethyl-N-methyl-N-propylammonium bis(fluorosulfonyl)imide, N,N-diethyl-N-methyl-N-propylammonium bis(fluorosulfonyl)imide, N,N-dimethyl-N-ethyl-N-(3-methoxypropyl)ammonium bis(fluorosulfonyl)imide, N,N-dimethyl-N-ethyl-N-(3-methoxypropyl)ammonium bis(trifluoromethanesulfonyl)imide, N,N-dimethyl-N-ethyl N,N-dimethyl-N-ethyl-N-phenylethylammonium bis(trifluoromethanesulfonyl)imide, N-ethyl-N,N-dimethyl-N-(2-methoxyethyl)ammonium bis(fluorosulfonyl)imide, N-ethyl-N,N-dimethyl-N-(2-methoxyethyl)ammonium bis(trifluoromethanesulfonyl)imide, N-tributyl-N-methylammonium bis(trifluoromethanesulfonyl)imide, N-tributyl-N-methylammonium bis(trifluoromethanesulfonyl)imide, N-tributyl-N-methylammonium dicyanamide, N-tributyl-N-methylammonium iodide, N-trimethyl-N-butyl ammonium bis(trifluoromethanesulfonyl)imide, N-trimethyl-N-butylammonium bromide, N-trimethyl-N-hexylammonium bis(trifluoromethanesulfonyl)imide, N-trimethyl-N-propylammonium bis(fluorosulfonyl)imide, N-trimethyl-N-propylammonium bis(trifluoromethanesulfonyl)imide, (N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium bis(fluorosulfonyl)imide, 1-butyl-1-methylpyrrolidinium bis(fluorosulfonyl)imide, 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-methyl-1- (2-methoxyethyl)pyrrolidinium bis(fluorosulfonyl)imide, N,N-diethyl-N-methyl-N-propylammonium bis(fluorosulfonyl)imide, N-ethyl-N,N-dimethyl-N-(2-methoxyethyl)ammonium bis(fluorosulfonyl)imide, N-propyl-N-methylpiperidinium bis(fluorosulfonyl)imide, N-trimethyl-N-butylammonium bis(fluorosulfonyl)imide, N-methyl-N-butyl-piperidinium bis(trifluoromethanesulfonyl)imide, N-methyl-N-propylpyrrolidinium bis(trifluoromethanesulfonyl)imide, and combinations thereof.

[0048] Alternatively or additionally, the liquid electrolyte may be a gel electrolyte. The gel electrolyte may comprise polyethylene oxide with a gelled liquid electrolyte, for example an ether such as dimethyl ether. In one embodiment, the electrolyte may comprise polyethylene oxide combined with LiTFSI in dimethyl ether.

[0049] Any combination of the above solvents may be used in the electrolyte. For example, the electrolyte may comprise a combination of an ionic liquid and a fluorinated ether, or a combination of an ionic liquid in a gel, or a combination of a fluorinated ether in a gel. Any other combination of two or more of the liquids and / or gels detailed above is contemplated.

[0050] In a preferred embodiment, the solvent is an ether, such as dimethoxyethane (DME), dioxolane (DIOX), diglyme, triglyme, tetraglyme or a mixture thereof. In another preferred embodiment, the solvent is a fluorinated ether.

[0051] In the case where the battery is a lithium-sulfur battery, the electrolyte comprises a lithium salt dissolved in a solvent. Suitable lithium salts include lithium hexafluoroarsenate LiAsF6, lithium hexafluorophosphate LiPF6, lithium perchlorate LiClO4, lithium sulfate Li2SO4, lithium nitrate LiNO3, lithium trifluoromethanesulfonate LiOTf, lithium bis(trifluoromethane)sulfonyl imide LiTFSI, lithium bis(fluorosulfonyl)imide LiFSI, lithium bis(oxalate)borate LiBOB, lithium difluoro(oxalate)borate LiDFOB, lithium bis(pentafluoroethanesulfonyl)imide LiBETI, 2-trifluoromethyl-4,5-dicyanoimidazole lithium LiTDI, and combinations thereof.

[0052] The electrolyte may comprise one or more lithium salts. Combinations of salts may be used, for example lithium triflate may be used in combination with lithium nitrate.

[0053] Alternatively, in the case where the battery is a sodium-sulfur battery, the electrolyte includes at least one sodium salt dissolved in an organic solvent. Suitable sodium salts include sodium hexafluoroarsenate, sodium hexafluorophosphate, sodium perchlorate, sodium sulfate, sodium nitrate, sodium trifluoromethanesulfonate, sodium bis(trifluoromethane)sulfonyl imide, sodium bis(fluorosulfonyl)imide, sodium bis(oxalate)borate, sodium difluoro(oxalate)borate, sodium bis(pentafluoroethanesulfonyl)imide, sodium 2-trifluoromethyl-4,5-dicyanoimidazole, and combinations thereof. The electrolyte may include one or more of the sodium salts. In one embodiment, the electrolyte may include a combination of a lithium salt and a sodium salt.

[0054] The electrolyte has a low solubility for polysulfides, or in some cases, the electrolyte may not dissolve polysulfides. The electrolyte may have a polysulfide solubility of less than 500mM at room temperature (20°C). For example, the electrolyte may have a polysulfide solubility of less than 400mM, preferably less than 200mM, more preferably less than 100mM, for example, less than 50mM, for example, less than 1mM at room temperature. Accordingly, the electrolyte may generally have a lower solubility for sulfur-containing substances (such as polysulfides and sulfur). For example, at room temperature (20°C), the electrolyte may have a sulfur solubility of less than 500mM. For example, at room temperature, the electrolyte may have a polysulfide solubility of less than 400mM, preferably less than 200mM, more preferably less than 100mM, for example, less than 50mM, for example, less than 1mM.

[0055] The lithium salt or sodium salt may be present in the electrolyte at a high concentration, i.e., at a level close to the saturation concentration of the electrolyte. For example, the concentration of the lithium or sodium salt in the electrolyte may be in the range of 0.05M-10M, preferably in the range of 1M-5M, such as 3M. ​​The concentration of at least one lithium or sodium salt in the solvent may be at least 75% of the saturation concentration of the solvent system, preferably at least 80% of the saturation concentration of the solvent, such as at least 85% of the saturation concentration of the solvent, such as at least 90% of the saturation concentration of the solvent. In one embodiment, the concentration of the solvent is about 100% of the saturation concentration, i.e., the electrolyte may be fully saturated.

[0056] The term "saturation concentration" is the degree of solubility of a particular substance in a particular solvent. When saturation concentration is reached, adding more solute (e.g., more lithium salt) will not increase the concentration of the solution. Instead, the excess solute will precipitate out of solution. Saturation concentration is measured at room temperature, e.g., 25°C.

[0057] The use of electrolytes with poor or no solubility for polysulfides, such as electrolytes containing lithium salts at near saturation concentrations, can inhibit the shuttling of polysulfides in the electrolyte and is therefore beneficial in batteries such as lithium-sulfur batteries. The shuttling effect of polysulfides is detrimental due to the resulting loss of coulombic efficiency. Without wishing to be bound by theory, the presence of highly concentrated electrolytes and lithium (or sodium) salts at concentrations close to saturation concentrations only allows a small amount of polysulfides to dissolve in the electrolyte, which means that little or no polysulfide shuttling can occur. Therefore, the concentration of alkali metal salts in the electrolyte means that the electrolyte has a low solubility for polysulfides. Due to the low utilization of active sulfur species, the use of electrolytes with lithium salts at concentrations close to saturation concentrations in "conventional" lithium-sulfur batteries often leads to poor electrochemical performance. This is because the intermediate species cannot be solvated by the electrolyte because the electrolyte is close to solvation. In conventional cathodes, without solvation of the intermediate species, lithium ions cannot be fully transferred to the active sulfur species present, which will therefore lead to greatly reduced utilization and performance under conventional operating conditions. However, the combination of a low porosity, solid cathode with an electrolyte with poor polysulfide solubility alleviates this problem due to the lack of dissolution of the polysulfides during cycling. In the present invention, electrolytes with poor polysulfide solubility, such as electrolytes containing salts at concentrations close to the saturation concentration of the electrolyte, can be effectively used in combination with a solid cathode. While in conventional high energy lithium-sulfur batteries the cathode requires a non-viscous electrolyte at a concentration far from the saturation concentration of the electrolyte, the chemistry involved in the present battery means that the electrolyte does not need to be non-viscous, and the concentration of the electrolyte does not have to be far from the saturation concentration of the dissolved lithium salt (or sodium salt, in the case of sodium-sulfur batteries).

[0058] Despite the low solubility of polysulfides in the electrolyte system, the combined use of the electrolyte and cathode according to the present invention allows a low volume of electrolyte to be used in the battery. In conventional lithium-sulfur batteries, an electrolyte with high solubility for the lithium polysulfide species is required, and the capacity of such a battery depends on the solubility and therefore on the volume of electrolyte available in the battery. High concentration electrolytes have low solubility for polysulfide intermediates. Therefore, if a high concentration electrolyte is used in combination with a conventional cathode, more electrolyte is required to achieve high capacity because more electrolyte is needed to dissolve the active material. A larger volume of electrolyte is disadvantageous because it will increase the size and weight of the battery and result in lower specific energy.

[0059] In the present invention, the chemical processes taking place in the cathode mean that the formation of polysulfides is suppressed or avoided, and therefore the capacity achievable by the battery during charge and discharge does not depend on the solubility and volume of the electrolyte. This allows the use of relatively small amounts of highly concentrated electrolyte to obtain high capacity. In one embodiment, about 0.1-3 microliters of electrolyte per gram of active sulfur, preferably 0.5-2 microliters of electrolyte per gram of active sulfur, for example 1 microliter of electrolyte per gram of active sulfur is present in a battery according to the present invention.

[0060] The use of highly concentrated electrolytes can also improve the performance of lithium metal anodes. For example, highly concentrated electrolytes can effectively passivate the anode, forming a stable solid electrolyte interface (SEI). This can make the battery cycle safe and can provide a long cycle life.

[0061] In addition to the lithium (or sodium) salts described in detail above, the electrolyte may also include other salts. For example, the electrolyte may include other metal salts such as sodium, lithium, potassium, rubidium, cesium, calcium, and magnesium salts. Examples of other salts include NaTFSI, KTFSI, RbTFSI, CsTFSI, Ca(TFSI)2, Mg(TFSI)2, NaPF6, and NaFSI. Other salts may be present in an amount of 1wt%-50wt%, preferably 5wt%-30wt%, for example, 10wt%-20wt% of the total amount of salt in the electrolyte.

[0062] method

[0063] The battery according to the present invention can be produced by any suitable method. For example, a mixture of electroactive sulfur materials can be mixed in the form of a slurry in a solvent (e.g., water or an organic solvent) and applied to a current collector. The electroactive sulfur material can be mixed with, for example, an ionically conductive material and / or an electrically conductive material and further optional components such as a binder before forming the slurry. The solvent can then be removed and the resulting structure calendered to form a composite structure, which can be cut into a desired shape to form a cathode. A separator can then be placed on the cathode, and an anode can be placed on the separator to form a stack, and then an electrolyte is added to form a battery.

[0064] Example

[0065] Example 1

[0066] The electrochemical performance of a lithium-sulfur battery with a "conventional" cathode is provided. The cathode (positive electrode) contains 70 wt% sulfur as an active material, 20 wt% Ketjen black as a conductive additive, and 10 wt% PEO as a binder. The liquid electrolyte of the battery contains a lithium salt at a concentration exceeding 75% of its saturation concentration. The liquid electrolyte consists of LiFSI dissolved in dimethoxyethane (DME) to a molar concentration of 4.5 M. A 100 micron thick lithium metal foil is used as the negative electrode (anode). The liquid electrolyte components are maintained in an inert separator placed between the electrodes.

[0067] Based on the total sulfur content of the cathode, measured by mass, and assuming a theoretical capacity of sulfur of 1672 mA·hg -1 , the cell was cycled between 1.5 V and 2.8 V at an applied current equivalent to a ratio of C / 50.

[0068] Figure 1 The electrochemical performance data of the battery are provided in.

[0069] Using electrolytes at >75% of their saturation concentration allows limiting the formation of polysulfide species. This reduces or prevents shuttling phenomena. However, the utilization of the active material is poor.

[0070] Example 2

[0071] Figure 2 The electrochemical performance data of the battery according to the present invention are provided in. The cathode (positive electrode) produced according to the present invention comprises 50 wt% of a solid ion-conducting ceramic (produced by combining 75 wt% of Li2S with 25 wt% of P2S5), 30 wt% of elemental sulfur as an active material and 10 wt% of Ketjen black as a conductive additive. The liquid electrolyte contains a lithium salt in a concentration greater than 75% of its saturation concentration and a lithium metal foil as an anode (negative electrode). The liquid electrolyte component is retained in an inert separator placed between the electrodes. The sulfur contained in the solid electrolyte component is taken into account in the capacity calculation.

[0072] In this cell, the utilization of active sulfur materials is significantly improved, the formation of soluble polysulfide species is suppressed, and no shuttling phenomenon is observed. Figure 3 Provided in Figure 1 and Figure 2 Comparison of the cycle 2 discharge curves of . This comparison shows that the cathode (positive electrode) described by the present invention, used in combination with an electrolyte at >75% of its saturation concentration, allows a significant improvement in performance compared to conventional types of sulfur cathodes. The present invention allows a high utilization of the active material while avoiding the formation of solvated polysulfide species, so that no shuttling phenomena are observed.

[0073] Throughout the description and claims of this specification, the words "comprise" and "comprising" and their variations mean "including, but not limited to", and they are not intended to (and do not) exclude other parts, additives, components, integers or steps. Throughout the description and claims of this specification, the singular encompasses the plural, unless the context requires otherwise. In particular, where the indefinite article is used, the specification should be understood as contemplating the plural as well as the singular, unless the context requires otherwise.

[0074] Features, integers, characteristics, compounds, chemical moieties or groups described in conjunction with a particular aspect, embodiment or example of the invention should be understood to be applicable to any other aspect, embodiment or example described herein unless incompatible therewith. All features disclosed in this specification (including any accompanying claims, abstract and drawings) and / or all steps of any method or process so disclosed may be combined in any combination, unless at least some of the combinations of such features and / or steps are mutually exclusive. The invention is not limited to the details of any foregoing embodiments. The invention extends to any novel feature or novel combination of features disclosed in this specification (including any accompanying claims, abstract and drawings), or to a novel step or novel combination of steps of any method or process so disclosed.

[0075] The reader's attention is directed to all papers and documents filed concurrently with or before this specification, which are related to this specification and are disclosed to the public with this specification, and the contents of all such papers and documents are incorporated herein by reference.

[0076] In particular, the present invention also relates to the following items:

[0077] Item 1. An electrochemical cell comprising:

[0078] an anode comprising lithium metal or sodium metal, or a lithium metal alloy or a sodium metal alloy;

[0079] an ionically conductive cathode comprising an electroactive sulfur material; and

[0080] A liquid electrolyte comprising at least one lithium salt or at least one sodium salt, wherein the polysulfide solubility of the electrolyte is less than 500 mM.

[0081] Item 2. The battery of Item 1, wherein the concentration of the at least one lithium salt or the at least one sodium salt in the electrolyte is at least 75% of the saturation concentration of the electrolyte.

[0082] Item 3. The battery according to Item 1, wherein the cathode further comprises an ion-conductive material selected from at least one of conductive ceramic particles and ion-conductive polymers.

[0083] Item 4. A battery according to Item 3, wherein the conductive ceramic particles are selected from at least one of LLZO, LATP, LGPS or Li2S-P2S5.

[0084] Item 5. The battery according to any one of the preceding items, wherein the cathode further comprises a solid conductive material, the solid conductive material comprising a conductive carbon material or an ion conductive polymer.

[0085] Item 6. A battery according to Item 5, wherein the conductive carbon material is selected from at least one of carbon nanotubes, carbon nanofibers, graphene, reduced graphene oxide and carbon black.

[0086] Item 7. The battery according to Item 5, wherein the ion-conductive polymer is selected from at least one of polypyrrole, polythiophene, polyaniline, polyacetylene, polyphenylene vinylene and poly(3,4-ethylenedioxythiophene).

[0087] Item 8. A battery according to Item 1, wherein the cathode comprises a carbon-sulfur composite material.

[0088] Item 9. The battery of any one of the preceding items, wherein the cathode comprises 1 to 60% by weight of the ion conductive material based on the total weight of the cathode.

[0089] Item 10. The battery according to any of the preceding items, wherein the electroactive sulfur material comprises elemental sulfur or Li2S.

[0090] Item 11. A battery according to any one of the preceding items, wherein the at least one lithium salt is selected from lithium hexafluoroarsenate LiAsF6, lithium hexafluorophosphate LiPF6, lithium perchlorate LiClO4, lithium sulfate Li2SO4, lithium nitrate LiNO3, lithium trifluoromethanesulfonate LiOTf, lithium bis(trifluoromethane)sulfonyl imide LiTFSI, lithium bis(fluorosulfonyl)imide LiFSI, lithium bis(oxalate)borate LiBOB, lithium difluoro(oxalate)borate LiDFOB, lithium bis(pentafluoroethanesulfonyl)imide LiBETI, 2-trifluoromethyl-4,5-dicyanoimidazole lithium LiTDI and combinations thereof.

[0091] Item 12. A battery according to any one of the preceding items, wherein the electrolyte comprises a solvent selected from linear ether, diethyl ether (DEE), tetrahydrofuran (THF), dimethoxyethane (DME), dioxolane (DIOX), diethylene glycol dimethyl ether, dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), methyl formate (MF), ethyl formate (EF), methyl propionate (MP), ethyl acetate (EA) and methyl butyrate (MB), methyl ethyl ketone, acetonitrile (ACN), propionitrile (PN), isobutyronitrile (iBN), dimethylformamide (DMF), dimethylacetamide (DMAc), N-methyl-2-pyrrolidone (NMP), tetramethyl urea (TMU), dimethyl sulfoxide (DMSO), trimethyl phosphate, triethyl phosphate, hexamethylphosphoramide, toluene, benzene, heptane, xylene and dichloromethane; at least one of ionic liquids, fluorinated ethers, gels and mixtures thereof.

[0092] Item 13. The battery according to any one of the preceding items, wherein the saturation concentration is at least 80%, preferably at least 90%.

[0093] Item 14. A battery according to any one of the preceding items, wherein the cathode further comprises a binder, and the binder is preferably selected from at least one of PEO, PVDF, Nafion, polypyrrole, polythiophene, polyaniline, polyacetylene, polyphenylene vinylene, poly(3,4-ethylenedioxythiophene) and polyphenylene sulfide.

[0094] Item 15. The battery according to Item 14, wherein the binder accounts for 1 to 30% by weight of the total weight of the electrode.

[0095] Item 16. The battery according to any one of the preceding items, wherein the polysulfide solubility of the electrolyte is less than 400 mM, preferably less than 200 mM, for example less than 100 mM.

[0096] Item 17. The battery according to any one of the preceding items, wherein the battery is a lithium-sulfur battery.

Claims

1. An electrochemical cell comprising: an anode comprising lithium metal or sodium metal, or a lithium metal alloy or a sodium metal alloy; an ionically conductive cathode comprising an electroactive sulfur material; and A liquid electrolyte comprising at least one lithium salt or at least one sodium salt, wherein the polysulfide solubility of the electrolyte is less than 500 mM.

2. The battery according to claim 1, wherein The concentration of the at least one lithium salt or the at least one sodium salt in the electrolyte is at least 75% of the saturation concentration of the electrolyte.

3. The battery according to claim 1, wherein The cathode further comprises an ion-conductive material selected from at least one of conductive ceramic particles and ion-conductive polymers.

4. The battery according to claim 3, wherein The conductive ceramic particles are selected from at least one of LLZO, LATP, LGPS or Li2S-P2S5.

5. A battery according to any one of the preceding claims, wherein The cathode also includes a solid electrically conductive material including an electrically conductive carbon material or an ionically conductive polymer.

6. The battery according to claim 5, wherein The conductive carbon material is selected from at least one of carbon nanotubes, carbon nanofibers, graphene, reduced graphene oxide and carbon black.

7. The battery according to claim 5, wherein The ion-conductive polymer is selected from at least one of polypyrrole, polythiophene, polyaniline, polyacetylene, polyphenylene vinylene and poly(3,4-ethylenedioxythiophene).

8. The battery according to claim 1, wherein The cathode comprises a carbon-sulfur composite material.

9. A battery according to any one of the preceding claims, wherein: The cathode includes 1 to 60% by weight of an ion conductive material based on the total weight of the cathode.

10. A battery according to any one of the preceding claims, wherein The electroactive sulfur material includes elemental sulfur or Li2S.

11. A battery according to any one of the preceding claims, wherein The at least one lithium salt is selected from lithium hexafluoroarsenate LiAsF6, lithium hexafluorophosphate LiPF6, lithium perchlorate LiClO4, lithium sulfate Li2SO4, lithium nitrate LiNO3, lithium trifluoromethanesulfonate LiOTf, lithium bis(trifluoromethane)sulfonyl imide LiTFSI, lithium bis(fluorosulfonyl)imide LiFSI, lithium bis(oxalate)borate LiBOB, lithium difluoro(oxalate)borate LiDFOB, lithium bis(pentafluoroethanesulfonyl)imide LiBETI, 2-trifluoromethyl-4,5-dicyanoimidazole lithium LiTDI and combinations thereof.

12. A battery according to any one of the preceding claims, wherein The electrolyte comprises a solvent selected from linear ether, diethyl ether (DEE), tetrahydrofuran (THF), dimethoxyethane (DME), dioxolane (DIOX), diethylene glycol dimethyl ether, dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), methyl formate (MF), ethyl formate (EF), methyl propionate (MP), ethyl acetate (EA) and methyl butyrate (MB), methyl ethyl ketone, acetonitrile (ACN), propionitrile (PN), isobutyronitrile (iBN), dimethylformamide (DMF), dimethylacetamide (DMAc), N-methyl-2-pyrrolidone (NMP), tetramethylurea (TMU), dimethyl sulfoxide (DMSO), trimethyl phosphate, triethyl phosphate, hexamethylphosphoramide, toluene, benzene, heptane, xylene and dichloromethane; at least one of ionic liquids, fluorinated ethers, gels and mixtures thereof.

13. A battery according to any one of the preceding claims, wherein The saturation concentration is at least 80%, preferably at least 90%.

14. A battery according to any one of the preceding claims, wherein The cathode further comprises a binder, wherein the binder is preferably selected from at least one of PEO, PVDF, Nafion, polypyrrole, polythiophene, polyaniline, polyacetylene, polyphenylene vinylene, poly(3,4-ethylenedioxythiophene) and polyphenylene sulfide.

15. The battery according to claim 14, wherein The binder accounts for 1 to 30% by weight of the total weight of the electrode.

16. A battery according to any one of the preceding claims, wherein The polysulfide solubility of the electrolyte is less than 400 mM, preferably less than 200 mM, for example less than 100 mM.

17. A battery according to any one of the preceding claims, wherein The battery is a lithium-sulfur battery.